2008
DOI: 10.1002/glia.20671
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of astrocytic metabolic phenotype by proinflammatory cytokines

Abstract: Astrocytes play an important role in nervous system homeostasis. In particular, they contribute to the regulation of local energy metabolism and to oxidative stress defence. In previous experiments, we showed that long-term treatment with interleukin 1alpha (IL-1alpha) or tumor necrosis factor-alpha (TNFalpha) alone increases glucose utilization in primary culture of mouse astrocytes. In our study, we report that a combination of IL-1beta and TNFalpha exerts a synergistic effect on glucose utilization and mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
121
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 70 publications
9
121
0
3
Order By: Relevance
“…Primary Astrocytes Culture and Immunocytochemistry-Primary cultures of hypothalamic and cortical astrocytes were prepared from 1-day-old C57Bl/6 pups using a protocol adapted from the group of Magistretti and co-workers (31). Briefly, after decapitation, the brains were removed, and the hypothalami and cortices were dissected and transferred into 6-well plates containing 2 ml of DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Primary Astrocytes Culture and Immunocytochemistry-Primary cultures of hypothalamic and cortical astrocytes were prepared from 1-day-old C57Bl/6 pups using a protocol adapted from the group of Magistretti and co-workers (31). Briefly, after decapitation, the brains were removed, and the hypothalami and cortices were dissected and transferred into 6-well plates containing 2 ml of DMEM.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of cerebral cortical astrocytes were prepared from newborn (1-to 2-d-old) OF1 mice (Charles River Laboratories) as previously described (Gavillet et al, 2008). Cells were plated in 35 mm dishes and maintained in DMEM (D7777, Sigma-Aldrich) containing 25 mM glucose and supplemented with 44 mM NaHCO 3 , 10 ml/L antibiotic/ antimycotic solution (Invitrogen), and 10% FCS (Bioconcept), and incubated at 37°C in an atmosphere containing 5% CO 2 and 95% air.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Numerous reports have shown that astrocytes display high metabolic plasticity in terms of glucose utilization, which is not the case for neurons (Pellerin and Magistretti, 1994;Almeida et al, 2001;Prapong et al, 2002;Porras et al, 2004;Gavillet et al, 2008;Allaman et al, 2010;BĂ©langer et al, 2011). One striking example is the differential response of astrocytes and neurons following the inhibition of mitochondrial respiration by NO.…”
mentioning
confidence: 99%
“…TNF-α can further influence astrocytes and microglia to release nitrogen and oxygen reactive species that cause oxidative stress to neurons and glial cells [6,67,112,116]. Such oxidative damage is particularly noticeable in Figure 4.…”
Section: Increase In Peripheral Blood Cytokine Levels Induced By Lipomentioning
confidence: 99%